Combined effect of knowledge management and entrepreneurial orientation on performance of small and medium enterprises - Abu Bakar, Hatinah; Mahmood, Rosli; Ismail, Nik Nor Hasimah (2014)
The aim of this research is to determine the effect of knowledge management and entrepreneurial orientation on performance of small-medium enterprises (SMEs) in Malaysia.The study also seeks to examine the mediating role of entrepreneurial orientation on the knowledge management and SME performance relationship. Data were collected by means of a mail survey questionnaire completed by the owner/managers who were randomly selected from a sampling frame of registered SMEs.A total of 115 usable responses were received.The findings reveal that significant relationships exist between knowledge management and performance, and also between entrepreneurial orientation and performance, while entrepreneurial orientation was found to partially mediate the relationship between knowledge management and performance.